Assessment of Enzymatic Browning and Evaluation of Antibrowning Methods on Dates - Mariam Al-Amrani; Ahmed Al-Alawi; Insaaf Al-Marhobi (International Journal of Food Science)
Dates’ color is known to play a crucial role in determining the value and quality of the fruit. The color changes from the natural accepted golden color to unfavorable dark brown color during storage. In this study, the effect of different color preservation methods (modified atmosphere packaging, cold storage (4°C), sulfur dioxide gas (SO2), and blanching) and its relation to darkening due to action of the browning enzymes and melanin production were investigated. Polyphenol oxidase was shown to be active in all treatments except the samples treated with SO2 gas and steam blanching for ten minutes. Likewise, peroxidase activity showed a similar trend in all samples, but a decrease in activity was observed in sulfated samples and total inactivation in steam blanching for ten minutes. Moreover, sulfated samples have shown improvement in color compared to all other treatments, whereas the steamed samples showed the highest color deterioration. Concurrently, melanin content increased in all samples over the period of storage except in the sulfated samples. FTIR analyses of dates’ melanin have revealed similar structural feature to the reference melanin; however, some differences were noticed in the regions 2850–2950 cm-1 and 1690–1705 cm-1 which indicated major structural difference between the two melanin samples. More work is suggested to reveal structural and functional properties of dates’ melanin.